Targeting dormant micrometastases: rationale, evidence to date and clinical implications - Hurst, Robert E.; Bastian, Anja; Bailey-Downs, Lora; Ihnat, Michael A. (Therapeutic advances in medical oncology, 2016)
In spite of decades of research, cancer survival has increased only modestly. This is because most research is based on models of primary tumors. Slow recognition has begun that disseminated, dormant cancer cells (micrometastatic cells) that are generally resistant to chemotherapy are the culprits in recurrence, and until these are targeted effectively we can expect only slow progress in increasing overall survival from cancer. This paper reviews efforts to understand the mechanisms by which cancer cells can become dormant, and thereby identify potential targets and drugs either on the market or in clinical trials that purport to prevent metastasis. This review targets the most recent literature because several excellent reviews have covered the literature from more than two years ago. The paper also describes recent work in the authors’ laboratories to develop a screening-based approach that does not require understanding of mechanisms of action or the molecular target. Success of this approach shows that targeting micrometastatic cells is definitely feasible.